Systematic Review Of Point Of Care Testing In Emergency Care - Nurjannah Nurjannah (Universitas Syiah Kuala, 2010)
Abstract. The study aims to review systematically the evidence of using Point of Care Testing (POCT) in Emergency Departments (EDs). It will identify and qualitatively synthesise whether POCT in emergency care is safe, effective and has effective outcomes for patients. The systematic review was based on principles and guidelines produced in the report by the National Institute for Health Research NIHR) Centre for Reviews and Dissemination (CRD), the University of York (2001) and the Critical Review Advisory Group (CRAG), by the School· of Health and Related Research (ScHARR), the University of Sheffield (1996). A thorough and systematic search strategy was adapted to identify, collate and .summanze a11 relevant studies the published research 1951 - 2008.There were 33 studies that met the inclusion criteria of the systematic review which consisted of 3 studies of Randomized Controlled Trial (RCT) design, 15 studies of diagnostic test design, 3 studies of before-and-after design and 12 articles of cohort design. There was clinical and methodological heterogeneity from all included studies. Thus, non-quantitative synthesis was performed. There is evidence that POCT in emergency care is safe, effective and bas effective outcomes for patients. In clinical outcomes, POCT may provide an independent and significant predictor for serious adverse events and death. However, POCT seems to be unlikely to reduce the mortality rate. In economical outcomes, POCT in EDs may decrease turnaround time and reduce unnecessary admission to hospital, in particular to Intensive Care Unit (ICU) and Coronary Care Unit (CCU), but there are inconsistencies in the results over reducing ED and hospital length of stay.(JKS2010;2:63-70)Key words: Point of Care Testing,EmergencyCare, EmergencyDepartment",